Teachers' Roles in Addressing Aggressive Behavior Through Social-Emotional Learning in Early Childhood Education - Siti Aisah; Novita Widiyaningrum (Fakultas Keguruan dan Ilmu Pendidikan, 2026)
Aggressive behavior in early childhood can hinder their social-emotional development. Teachers play a key role in addressing this thru Social and Emotional Learning (SEL). This qualitative case study research aims to examine the role of teachers in managing aggressive behavior at RA Al Abror, Gresik. Data was collected thru interviews with teachers and observations of children aged 4-6 years. The research findings revealed two manifestations of aggressive behavior: verbal (such as arguing and teasing) and non-verbal (such as hitting and damaging objects). The contributing factors include incorrect parenting styles, lack of emotional management skills, a non-conducive family environment, and biological factors. The role of a teacher includes creating a safe environment, identifying behaviors, implementing management strategies, teaching social-emotional skills, and collaborating with parents and professionals. It is concluded that effective PSE implementation requires a deep understanding of the causes of aggression, appropriate strategies, and multi-stakeholder collaboration to create a supportive learning environment.